Empresarios, ambiente, territorio y redes. Las nociones culturales y su construcción social. (2016)
This paper makes a reflection on the relationship between organizational culture, environmental and building networks, since a theoretical framework from organizational, geographical and sociological theories, which seeks to uncover the relating between networking and cultural notions of entrepreneurs, emphasizing a critical issue in today’s society: the environmental problem from structured aspects from corporate social responsibility (CSR).This document consists in three sections ranging from the contextualization of the entrepreneur in the modern structure, the cultural phenomena of entrepreneurs and the notion of network and recreated in the light of the two previous territory, allowing express from building networks the same as socio-technical structure from the creation of partnerships between entrepreneurs and their stakeholders.